Elimination of the Early Inhibition of Protein Synthesis in Escherichia coli C3000 Infected with Purified R17 Bacteriophage - Scott, John W. (1974)
Infection of Escherichia coli with an R17 bacteriophage suspension has been reported to result in early and late phases of inhibition of host protein synthesis (Yamazaki, 1969; Watanabe and Watanabe, 1968). However, early inhibition was observed when cultures were inoculated with only tryptone broth, which is often used to suspend R17 bacteriophage. Since early inhibition was not observed when E. coli cultures were inoculated with R17 bacteriophage suspended in phosphate buffer, early inhibition is not an intrinsic feature of R17 phage infection.